2023
DOI: 10.7324/japs.2023.117043
|View full text |Cite
|
Sign up to set email alerts
|

Optimization of Graptophyllum pictum leaves extraction using a simplex centroid design focused on extracting flavonoids with antioxidant activity

Abstract: Graptophyllum pictum (L.) Griff, which is called "daun ungu" in Indonesia, is a medicinal plant that contained flavonoids with antioxidant activity. The different extractor solvents (water, acetone, methanol, and ethanol) and their combinations were studied using a simplex centroid design through the Design Expert 13.0 program. From the optimized crude extract, it was investigated for total flavonoid content (TFC) using the colorimetric method (AlCl 3 ), as well as the antioxidant activity using 2,2-diphenyl-1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 3 publications
0
7
0
Order By: Relevance
“…The experimental method closely followed the procedures outlined in a previous study by Makkiyah et al 18 The simplex centroid design was employed using Design Expert software, comprising 4 solvent components (water, acetone, methanol, and ethanol) to optimize the extraction of P. oleracea. The extraction process was carried out by combining 4 grams of purslane aerial parts with 40 mL designated solvent, as shown in Table 1.…”
Section: Experimental Design and Extractionmentioning
confidence: 99%
See 1 more Smart Citation
“…The experimental method closely followed the procedures outlined in a previous study by Makkiyah et al 18 The simplex centroid design was employed using Design Expert software, comprising 4 solvent components (water, acetone, methanol, and ethanol) to optimize the extraction of P. oleracea. The extraction process was carried out by combining 4 grams of purslane aerial parts with 40 mL designated solvent, as shown in Table 1.…”
Section: Experimental Design and Extractionmentioning
confidence: 99%
“…14 Several studies also successfully applied SCD to optimize the extraction process of various plant materials, including Curcuma aeruginosa RoxB., 15 cardamom fruit, 16 Justicia gendarussa Burm.f, 17 and purple leaves (Graptophyllum pictum). 18 Despite the significant pharmacological potential of purslane, there are limited reports on optimizing the extraction solvent for total phenolic content (TPC) and antioxidant capacity in the extract. This indicates that the exploration to identify the ideal solvent or combination of solvents to achieve the highest TPC, coupled with potent antioxidant capacity remains largely unexplored.…”
Section: Introductionmentioning
confidence: 99%
“…The extraction of samples was conducted using sonication-maceration techniques, using previously established methodologies with minor adjustments. 15 To provide a concise overview, the experimental procedure involved the mixing of 30 g of the sample with 150 mL of solvent, as specified in Table 1. The combination underwent sonication (Decon F5 Major, Decon Laboratories, US) for a duration of 30 minutes, followed by maceration for a period of 3 h in a water bath shaker (DAIHAN WiseBath, South Korea) maintained at a temperature of 30°C.…”
Section: D-optimal Design and Extractionmentioning
confidence: 99%
“…Nonetheless, the process is subject to various factors such as the choice of extraction solvents, the ratio of sample to solvent, the duration and method of extraction, as well as the physical and chemical characteristics of the sample matrix. [15][16][17] The existing research does not present a consensus regarding a singular, effective standard extraction procedure or the optimal extraction solvent. Multiple studies have found that solid-liquid extraction employing various solvents is the most efficient method, with solvents of higher polarity often exhibiting enhanced solubility of polyphenols in the extraction process.…”
mentioning
confidence: 99%
“…The conventional method for designing these mixtures is manual, in which the solvent conditions are determined manually. [ 8 ] There are also more complex methods, such as statistical applications, such as simplex-lattice, simplex-centroid, or D-optimal design. The D-optimal design has been used in various fields, including the formulation of hard candy with antiviral herbal extracts, development of tablet formulations as dietary supplements, and determination of the combination of cassava and coconut composite flour for high-quality fillers in chicken sausages.…”
Section: Introductionmentioning
confidence: 99%